Dissolved gas and solute concentrations in surface and soil waters of an Arctic water track, Upper Kuparuk River Basin, Alaska, 2013 - Tamara Harms (Arctic Data Center)
This research evaluates how climate-induced changes in water and nutrient cycles on land are propagated to stream networks. Increased export of water and the nutrients nitrogen and phosphorus from river networks to the Arctic Ocean reflects shifts in patterns of water and nutrient movement in the arctic. Changing climate may contribute to such shifts by causing release of nutrients from thawing permafrost, altering precipitation patterns, increasing rates of biogeochemical reactions, or expanding storage capacity in thawed soils. These changes may have far-reaching effects because flowing water connects land to downstream aquatic ecosystems, but the flowpaths connecting terrestrial ecosystems to stream networks remain poorly understood. This research focuses on transport and reaction of water and solutes within water tracks, which are linear regions of surface and subsurface flow that connect hill slopes to streams and account for up to 35% of watershed area in arctic tundra. Specific objectives are to: 1) quantify sources of water and dissolved nutrients to water tracks, 2) identify effects of snow accumulation, thaw depth, and storm characteristics on storage and transport of water and solutes, and 3) estimate the effects of hydrology on rates of nutrient cycling in water tracks. This dataset contains measurements of dissolved concentrations of carbon dioxide, methane, and nitrous oxide, measured in surface and subsurface water collected from an Arctic water track. Samples were collected from a semi-regular grid of ~30 meters length and spanning the width of the water track channel.